2021
DOI: 10.1038/s41598-021-88021-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifreeze protein from Ammopiptanthus nanus functions in temperature-stress through domain A

Abstract: Temperature stress restricts plant growth and development. Antifreeze protein (AFP) can improve plants antifreeze ability. In our previous study, the AnAFP gene cloned from Ammopiptanthus nanus was confirmed to be an excellent candidate enhancing plant cold resistance. But, AnAFP protein shared similar structures with KnS type dehydrins including K, N and S domains except ice crystal binding domain A. Here, we generated AnAFPΔA, AnAFPΔK, AnAFPΔN and AnAFPΔS, and transformed them into ordinary and cold sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…For example, PtrICE1 modulates the levels of polyamines by interacting with ARGININE DECARBOXYLASE (PtADC), resulting in increased cold stress tolerance in transgenic lemons. Cheng first reported that Arachis hypogaea AnICE1 might regulate the expression of AnCBF2 , thereby enhancing the cold stress resistance of transgenic Arabidopsis . Another study revealed the interaction between the K domains of ANTIFREEZE PROTEIN (AnAFP) and AnICE1. , HbJAZ1/12 proteins interact with HbICE2 to attenuate the transcriptional function of HbICE2, subsequently inhibiting the expression of downstream genes in rubber tree. , The same research group also discovered EcaSIZ1 and EcaHOS1, which interact with EcaICE1 in enhancing cold tolerance. , Other research groups reported that TaMYC2D forms a ternary complex with TaICE41 and TaJAZ7 thus regulating freeze tolerance . Overall, further studies are needed to better understand the functional significance of bHLH protein dimerization in enhancing the cold tolerance in plants.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, PtrICE1 modulates the levels of polyamines by interacting with ARGININE DECARBOXYLASE (PtADC), resulting in increased cold stress tolerance in transgenic lemons. Cheng first reported that Arachis hypogaea AnICE1 might regulate the expression of AnCBF2 , thereby enhancing the cold stress resistance of transgenic Arabidopsis . Another study revealed the interaction between the K domains of ANTIFREEZE PROTEIN (AnAFP) and AnICE1. , HbJAZ1/12 proteins interact with HbICE2 to attenuate the transcriptional function of HbICE2, subsequently inhibiting the expression of downstream genes in rubber tree. , The same research group also discovered EcaSIZ1 and EcaHOS1, which interact with EcaICE1 in enhancing cold tolerance. , Other research groups reported that TaMYC2D forms a ternary complex with TaICE41 and TaJAZ7 thus regulating freeze tolerance . Overall, further studies are needed to better understand the functional significance of bHLH protein dimerization in enhancing the cold tolerance in plants.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 97%
“…Another study revealed the interaction between the K domains of ANTIFREEZE PROTEIN (AnAFP) and AnICE1. 2830,211 HbJAZ1/12 proteins interact with HbICE2 to attenuate the transcriptional function of HbICE2, subsequently inhibiting the expression of downstream genes in rubber tree. 90,91 The same research group also discovered EcaSIZ1 and EcaHOS1, which interact with EcaICE1 in enhancing cold tolerance.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
“…These apoplastic extracts changed the ice-crystal morphology and had thermal hysteresis characteristics unique to the AFPs found in the animal kingdom. Since then, AFPs have been reported from more than 60 plants, including monocots, dicots, and gymnosperms (Smallwood et al, 1999;Wisniewski et al, 1999;Kuiper et al, 2001;Kawahara et al, 2009;Lauresen et al, 2011;Gupta and Deswal, 2012;Wang Q. et al, 2020;Arya et al, 2021;Yu et al, 2021). The AFPs from plants are different from the AFPs reported in animals in that it does not act as a cryoprotectant but as an ice interacting protein (Griffith et al, 2005).…”
Section: Plant Antifreeze Proteinsmentioning
confidence: 99%
“…In this purification method, the crude hydrolysate falls on a chilled vertical surface of a commercial ice machine; ice-binding proteins binds to the ice, whereas non-ice-binding proteins do not bind to ice. Many plant species have been used for isolation, purification, and identification of AFPs, such as bittersweet nightshade, winter rye, carrot, ryegrass, malting barley, oat, Hipphoae rhamnides, Brassica juncea, and Ammopiptanthus nanus (Griffith et al, 1992b;Gupta and Deswal, 2012;Ding et al, 2014;Ding et al, 2015;Arya et al, 2021;Yu et al, 2021). Further, nanolitre osmometry, differential scanning calorimeter, sucrose sandwich splat assay, and capillary assays are used to detect antifreeze activity in the AFPs extract /purified AFPs based on how AFP changes the growth of ice crystals.…”
Section: Extraction Purification and Identification Of Antifreeze Pro...mentioning
confidence: 99%
“…A very valuable relict plant, A. nanus is the Leguminaceae family and is a solo broadleaved evergreen plant in the desert region of northwest China [15]. It is only found in a limited area in Kyrgyzstan [16] and in the Wuqia County of China, at an altitude of 2000-2400 m [15,17], growing on sunny arid slopes with 138 mm of average annual precipitation, 2580 mm of annual average evaporation, a 35 °C extreme maximum temperature, and a −30 °C of extreme minimum temperature, and is considered a super-arid plant with outstanding biological properties of drought tolerance [18] and cold tolerance [19][20][21] as well as the ecological values of wind protection, sand fixation, and prevention of soil erosion; its flower number is large, and its yellow corolla and "explosive" opening pattern in a short time has high ornamental value (Figure 1); its stems and leaves are rich in alkaloids, flavonoids, and phenylpropanoids [22], which were traditionally used for medicinal purposes; and it also has important academic value in the study of paleoclimatic changes. However, climate change and long-term anthropogenic and natural disturbance events have resulted in a thin population of the species, with only six small, isolated surviving populations [23][24][25], and the species is listed as a national endangered plant in China.…”
Section: Introductionmentioning
confidence: 99%